Trends in the Incidence of Spontaneous Subarachnoid Hemorrhages in the United States, 2007–2017. (10th January 2023) - Xia, Christina; Hoffman, Haydn; Anikpezie, Nnabuchi; Philip, Karan; Wee, Claribel; Choudhry, Reema; Albright, Karen C.; Masoud, Hesham; Beutler, Timothy; Schmidt, Elena; Gould, Grahame; Patel, Smit D.; et al.
Abstract : Background and Objective: To test the hypothesis that age-specific, sex-specific, and race-specific and ethnicity-specific incidence of nontraumatic subarachnoid hemorrhage (SAH) increased in the United States over the last decade. Methods: In this retrospective cohort study, validated International Classification of Diseases codes were used to identify all new cases of SAH (n = 39, 475) in the State Inpatients Databases of New York and Florida (2007–2017). SAH counts were combined with Census data to calculate incidence. Joinpoint regression was used to compute the annual percentage change (APC) in incidence and to compare trends over time between demographic subgroups. Results: Across the study period, the average annual age-standardized/sex-standardized incidence of SAH in cases per 100, 000 population was 11.4, but incidence was significantly higher in women (13.1) compared with that in men (9.6), p < 0.001. Incidence also increased with age in both sexes (men aged 20–44 years: 3.6; men aged 65 years or older: 22.0). Age-standardized and sex-standardized incidence was greater in Black patients (15.4) compared with that in non-Hispanic White (NHW) patients (9.9) and other races and ethnicities, p < 0.001. On joinpoint regression, incidence increased over time (APC 0.7%, p < 0.001), but most of this increase occurred in men aged 45–64 years (APC 1.1%, p = 0.006), men aged 65 years or older (APC 2.3%, p < 0.001), and women aged 65 years or older (APC 0.7%, p = 0.009). Incidence in women aged 20–44 years declined (APC −0.7%, p = 0.017), while those in other age/sex groups remained unchanged over time. Incidence increased in Black patients (APC 1.8%, p = 0.014), whereas that in Asian, Hispanic, and NHW patients did not change significantly over time. Discussion: Nontraumatic SAH incidence in the United States increased over the last decade predominantly in middle-aged men and elderly men and women. Incidence is disproportionately higher and increasing in Black patients, whereas that in other races and ethnicities did not change significantly over time.